Aminolysis of styrene oxide catalyzed by microporous silica with longitudinal and spiral pore channels prepared from rice husk ash. (2018) - Iqbal, Anwar; Hou, T.K.; Shaari, U.S.; Adam, Farook; Abu Bakar, N.H.H; Wilson, L.D.; Jaafar, N.F.; Hazwan Hussin, M.; Afandi, M.A.
Abstract: An amorphous silica catalyst (MS-AI) with longitudinal and spiral pore channels was prepared from rice husk ash via sol-gel method. The BET surface area of MS-AI was 1016 m 2 g -1, while NLDFT results indicate that the pore size of MS-AI was variable: ultramicropore (6 Å) and supermicropore (11- 20 Å). The t -plot results indicate an estimated micropore surface area of 947 m 2 g -1 with a micropore volume of 0.41 cm 3 g -1 . The presence of the Q 2 signal along with the Q 3 and Q 4 signals indicate the condensation of silanol groups to siloxane groups within the framework of the catalyst is incomplete. The catalytic activity was tested for the aminolysis of styrene oxide with aniline. The reaction is proposed to take place via hydrogen bond interactions between the surface silanol bonds of the catalyst with styrene oxide. High levels of conversion of styrene oxide (92-95 %) occurred at 50 °C for 4 hours. The catalyst was selective towards ß-amino alcohol (96.8-98.5 %) where benzalaniline was the minor product obtained.